In-source laser spectroscopy of Cu-75,Cu-77,Cu-78: Direct evidence for a change in the quasiparticle energy sequence in Cu-75,Cu-77 and an absence of longer-lived isomers in Cu-78 - Koester, U; Stone, N; Flanagan, K; Stone, JR; Fedosseev, V; Kratz, K; Marsh, B; Materna, T; Mathieu, L; Molkanov, P; Seliverstov, MD; Serot, O; et al. (2011)
This paper describes measurements on the isotopes 75,77,78Cu by the technique of in-source laser spectroscopy, at the ISOLDE facility, CERN. The role of this technique is briefly discussed in the context of this and other, higher resolution, methods applied to copper isotopes in the range 57-78Cu. The data, analyzed in comparison with previous results on the lighter isotopes 59,63Cu, establish the ground-state nuclear spin of 75,77Cu as 5/2 and yield their magnetic dipole moments as +1.01(5)μN and +1.61(5)μN, respectively. The results on 78Cu show no evidence for long-lived isomerism at this mass number and are consistent with a spin in the range 3-6 and moment of 0.0(4) μN. ©2011 American Physical Society.